Emergency conditions, force and the repercussions of the Corona pandemic on civil and procedural obligations in Egyptian legislation - Suleiman, Mahmoud Sayed Ahmed Ibrahim (Journal of Risk and Crisis Management, 2021)
The Corona pandemic has repercussions for civil obligations in contracts and overstepping obligations, as well as for procedural obligations and what it contains from court hearings, appeals against rulings, and others.Through studying the theories of emergency conditions and force majeure, it was found that the Corona virus incident, "Covid 19", was one of the incidents of emergency conditions theory according to what we mentioned in the research, and not among the incidents and cases of force majeure.This research was followed by a conclusion that included the most important findings, recommendations and references.
Keywords: Corona pandemic; Egyptian law; Debtor obligations; Procedural obligations